The Determinant Factors of Family Dining Out Behaviours - Wiastuti, Rachel Dyah; Thalia Mizutani, Alexandra; Wiyana, Tri; Adiati, Maria Pia; Rashid, Basri (Journal of Business on Hospitality and Tourism, 2024)
This study aims to identify the determinant factors for family dining out behaviors. The primary data was collected from face to face questionnaire to 136 samples with sampling criteria sampling as such family status, Indonesian, and had minimum one dining out experience in the restaurant premises. Data was then analyzed with statistic descriptive and factor analysis. The findings showed that food taste, lack of time, and craving for specific food determined family the most upon deciding to dine out in the restaurant. Meanwhile, younger family tend to be determined more by food quality, while the older by lack of time. Further, despite the family background occupation either as paid- worker or employee, entrepreneur or housewife, all are determined the most by lack of time and food variability. In contrast, least determinant factor were calories consideration, advertisement, and other influenced. It can be concluded that different demographic led to different determinant factors that stimulate family to dine out. In addition, new five factors are formed from the previous eight factors consist of 17 items, which are as health, quality, lifestyle, convenience, and promotion. This study contributes to the of food and beverage literature that emphasizes for specific market of family during dining out in the restaurant